Sustainable Buildings Interaction Between a Holistic Conceptual Act and Materials Properties - Almusaed, Amjad; Almssad, Asaad (IntechOpen, 2018)
This book has been written to represent the efficient applications of sustainability upon building designs. The book intends to illustrate various techniques of action of sustainability on building conceptions. The book is divided into four parts and eight chapters. Part I "Introduction into Target Theme" includes a chapter with title "Introductory Chapter." It makes an overview of the meaning and the target of sustainable building and sustainable building material. Part II "Sustainable Building Design, Process, and Management" discusses many forms and concepts of sustainable building and includes three chapters. Part III "Sustainable Building by Using Energy Efficiency in Building Design" includes one chapter. Part IV "Sustainability in Building Materials: Study Cases" includes three chapters.